2016
DOI: 10.18668/ng.2016.11.03
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the statistical similarity of the physicochemical measurement data of shale formations based on the methods of cluster analysis

Abstract: Determination of the statistical similarity of the physicochemical measurement data of shale formations based on the methods of cluster analysisThe paper presents the application of the methods of statistical analysis to the determination of the similarity of measurement data, using boreholes providing access to shale formations as an example. The proposed methodology is based on two statistical techniques: the factor analysis and the cluster analysis. The first method allows the reduction of the number of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The classification of objects is based on a cluster analysis, where the focus is on the issue of generating clusters that are grouped into samples in gas, condensate and oil windows [29]. The characteristic geochemical properties of the samples classified into selected clusters are also determined [30]. Researchers successfully classified the samples into individual windows and determined their percentages in Silurian, Ordovician and Cambrian units.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…The classification of objects is based on a cluster analysis, where the focus is on the issue of generating clusters that are grouped into samples in gas, condensate and oil windows [29]. The characteristic geochemical properties of the samples classified into selected clusters are also determined [30]. Researchers successfully classified the samples into individual windows and determined their percentages in Silurian, Ordovician and Cambrian units.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…Cluster analysis methods have also been applied to investigate the similarity of samples described with geochemical parameters. One of the key issues presented in these works was the identification of rocks with similar total organic carbon (TOC) values [39][40][41]. The results demonstrated that it is possible to group the samples assigned to gas, condensate, and oil windows through cluster analysis.…”
Section: Introductionmentioning
confidence: 99%